Aesthetics of composition by Vincent Van Gogh and Degas and its impact on the development of artistic taste among students (Journal of the College of Basic Education, 2022)
Art is an emotional and influential means, and art is not the search for typical forms of beauty and the return to the basic principle that it must stem from basic needs in order to express our feelings towards the world around us with strong emotional actions that make us tend to evaluate the artwork on the basis of its vitality and activity. Art supports that artists generally rely on their sensory perceptions, especially visual ones, in their dealings with the social and natural environment in which they live and in their perception of it more than their reliance on symbols and abstract expressions, even if they sometimes use them to convey their delicate sensory feelings) and that dealing with artwork requires a good knowledge of the rules of art derived from the elements and foundations and how to use them in a positive way, away from the looseness and repetition that leads to uniqueness and change according to the visual scientific rule, which is based on all directions and artistic schools, as the artistic elements have rules and these rules have many advantages.